Analisis Kebijakan Promosi dalam Meningkatkan Volume Penjualan Mobil Merek Canter (Studi Kasus pada PT. Mitsubishi Andalas Berlian Motor Padang) - D Delvianti (Journal of Economics and Management Scienties, 2022)
This study aims to examine and analyze promotion policies in increasing sales of Canter brand cars (a case study at PT. Mitsubishi Andalas Berlian Motor Padang). The analytical method in this study uses the classical assumption test which consists of a normality test and a simple regression test, t test. The results of this study are partially the promotion cost policy at PT. Mitsubishi Andalas Berlian Motor Padang did not have a significant effect on sales volume at PT. Mitsubishi Andalas Berlian Motor Padang